2019
DOI: 10.33602/mebm.2.2.6
|View full text |Cite
|
Sign up to set email alerts
|

The association between maternal anthropometry and blood pressure in pregnancy – results from the Croatian islands’ birth cohort study (CRIBS)

Abstract: Elevated blood pressure (BP) in pregnancy, especially gestational hypertension and preeclampsia, can lead to serious pregnancy complications and adverse birth outcomes. A large body of literature already reported the effect of baseline body mass index (BMI) on changes in blood pressure during pregnancy. The aim of this study was therefore to define trajectory of systolic (SBP) and diastolic (DBP) blood pressure in 308 pregnant participants from the CRIBS study (146 from the mainland and 162 from the islands of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…Although preliminary results of the Croatian Islands' Birth Cohort Study (CRIBS) reported general adherence of pregnant women to the Mediterranean dietary pattern in a small sample of participants [21], a comprehensive study on dietary habits in Croatian pregnant women (especially on the islands) is still lacking. Other CRIBS results also confirmed the differences between Croatian island and mainland population, suggesting adverse socioeconomic and lifestyle conditions in the insular population [22,23]. This is in line with previous reports which indicated a greater burden of cardiovascular disease (CVD) risk factors in the population from the rural areas of Croatia [24,25].…”
Section: Introductionsupporting
confidence: 89%
“…Although preliminary results of the Croatian Islands' Birth Cohort Study (CRIBS) reported general adherence of pregnant women to the Mediterranean dietary pattern in a small sample of participants [21], a comprehensive study on dietary habits in Croatian pregnant women (especially on the islands) is still lacking. Other CRIBS results also confirmed the differences between Croatian island and mainland population, suggesting adverse socioeconomic and lifestyle conditions in the insular population [22,23]. This is in line with previous reports which indicated a greater burden of cardiovascular disease (CVD) risk factors in the population from the rural areas of Croatia [24,25].…”
Section: Introductionsupporting
confidence: 89%
“…All data from the CRIBS cohort are pregnancy-adjusted. More detailed descriptions of collected anthropometric, clinical and laboratory data from both cohorts are summarized in previous studies [18][19][20][21].…”
Section: Methodsmentioning
confidence: 99%